Child sexual abuse in the Eastern Health Board region of Ireland in 1988: an analysis of 512 confirmed cases - McKeown, Kieran; Gilligan, Robbie (Economic & Social Studies, 1991)
This paper reports some of the findings of a study of child sexual abuse in the Eastern Health Board region of Ireland. Data were supplied by Community Care Social Workers on all cases (990) known to them in 1988. By year end 512 of this total had been classified as confirmed on the basis of nationally agreed procedures; various findings for this group are presented. Three out of 4 victims were female; 1 in 4 male. The mean age of victims was 9.2 for girls and 7.0 for boys. In 60 per cent of cases the child was related to the abuser.
Keywords: Child sexual abuse; Eastern Health Board; Social services; Ireland